Cathepsin B is a New Drug Target for Traumatic Brain Injury Therapeutics: Evidence for E64d as a Promising Lead Drug Candidate - Hook, Gregory; Jacobsen, J. Steven; Grabstein, Kenneth; Kindy, Mark; Hook, Vivian (Frontiers in Neurology, 2015)
There currently is no therapeutic drug treatment for traumatic brain injury (TBI) despite decades of experimental clinical trials. This may be because the mechanistic pathways for improving TBI outcomes have yet to be identified and exploited. As such, there remains a need to seek out new molecular targets and their drug candidates to find new treatments for TBI. This review presents supporting evidence for cathepsin B, a cysteine protease, as a potentially important drug target for TBI. Cathepsin B expression is greatly up-regulated in TBI animal models, as well as in trauma patients. Importantly, knockout of the cathepsin B gene in TBI mice results in substantial improvements of TBI-caused deficits in behavior, pathology, and biomarkers, as well as improvements in related injury models. During the process of TBI-induced injury, cathepsin B likely escapes the lysosome, its normal subcellular location, into the cytoplasm or extracellular matrix (ECM) where its unleashed proteolytic power causes destruction via necrotic, apoptotic, autophagic, and activated glia-induced cell death, together with ECM breakdown and inflammation. Significantly, chemical inhibitors of cathepsin B are effective for improving deficits in TBI and related injuries including ischemia, cerebral bleeding, cerebral aneurysm, edema, pain, infection, nephritis, epilepsy, rheumatoid arthritis, pancreatitis, Huntington’s disease, and Alzheimer’s disease. The inhibitor E64d shows prominent efficacy for amelioration of TBI-caused deficits in preclinical models. In clinical trials, E64d has been shown to be safe based on its toxicological profile and, thus, illustrates the compound as an excellent candidate for drug development. These data support the overall conclusion that drug development of cathepsin B inhibitors, with E64d or a novel analog as a lead drug candidate, should be accelerated to improve the outcomes of TBI and related injuries.